Knowledge, attitudes, and practices towards COVID-19 among hospital staff of West Bengal during COVID-19 outbreak: A hospital based cross sectional study - Acharyya, Amitava; Ghosh, Susmita; Ghosh, Manas; Sarkar, Kalyan; Ghosh, Sonali; Bhattacharya, Ambarish; Ghosh, Kaushik (Asian Journal of Medical Sciences, 2020)
Background: COVID-19 disease is a highly contagious and totally unknown disease which is caused by SARS-CoV-2. This disease spread throughout the world irrespective of social, economical and political variation. Health care staff are the frontline COVID-19 worrier and their understanding of this disease is very important. Aims and Objective: The aim of this study was to assess the knowledge, attitudes and practices (KAP) towards COVID-19 disease among the healthcare staff of a tertiary care hospital of West Bengal. Materials and Methods: An analytic cross-sectional study was conducted at Murshidabad Medical College, Murshidabad from 25th April, 2020 to 2nd May, 2020. A total of 214 health care staff (83 nurses, 75 doctors, 20 para-medical staff, 24 administrative staff, and 12 sweepers) participated in this questionnaire based KAP study. The questionnaire was prepared according to the World Health Organization’ on Corona virus disease (COVID-19) “advice for the public”. The Systematic random sampling procedure was employed for data collection. The data was analysed using T-test, ANOVA, chi-square test and regression model. The informed consent was taken from each participant. Result: Female (62%) participants were more than male (38%) participants. Mean age of the participants was 27.03±7.63 years. About the half participants were unmarried (55%) and studied up to bachelor’s degree (49%). The overall knowledge score found to be “medium level” with 77% reporting correct answers. The knowledge score was statistically different among age group, education level, marital status and occupational group of health care staff in this hospital by univariate analysis. The good attitudes and good practices were not related with knowledge score. The majority of the respondents (78%) had confidence on their attitude that “India can win the battle against COVID-19”. Only 86% participants wore masks while going out in the lock-down period and 79% participants had not visited any crowded place. Only 18% participants used traditional home remedies for flu like symptoms. In multivariate analysis, doctors were found with better knowledge score and attitude towards COVID-19 than other healthcare staff in this hospital. Conclusion: The two preventive practice (social isolation and mask use) and optimistic attitude towards COVID-19 of health care staff were not totally depended on COVID-19 related knowledge score. However, knowledge score was depended on marital status, educational background, age, occupation and place of residence. Government should emphasize more on COVID-19 related health education and health promotion programme at community level.